Revision of the Brazilian Amazon Basin species of Porphyrochroa Melander (Diptera: Empididae) - Mendonça, Mirian Nascimento; Rafael, José Albertino; Ale-Rocha, Rosaly (Zootaxa, 2008)
The Brazilian Amazon Basin species of Porphyrochroa Melander are revised and include seventeen species: P. aliena, sp. nov., P. amazonica, sp. nov., P. bifida, sp. nov., P. cercosingularis, sp. nov., P. dactiloides, sp. nov., P. distincta, sp. nov., P. epandrialis, sp. nov., P. grandis, sp. nov., P. longiseta, sp. nov., P. manauara, sp. nov., P. neblina, sp. nov., P. pacaraima, sp. nov., P. platypoderis, sp. nov., P. quadrilamelaris, sp. nov., P. roraimensis, sp. nov., P. simplex sp. nov. and P. xavieri sp. nov. All species are described and male genitalia illustrated; these structures presented many characters with great systematic values. Copyright © 2008 Magnolia Press.
Keywords: Diptera; Empididae; Empidinae